2013
DOI: 10.1002/pc.22408
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of electropolymerized molecularly imprinted microporous polyaniline films for solar cell applications

Abstract: The solicitude to molecularly imprinted conjugated polymers is flourishing due to their auspicious properties for a myriad of technological and industrial applications. The preparation conditions strongly affect the structure, optical, thermal, and electrical properties of these polymers. Subsequently, a consistent contemplation is desired to entrench consanguinity between processing stipulations and these variables. Here, molecularly imprinted polyaniline films, based ascorbic acid as a template, have been sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…. As largely reported in the literature, either experimentally or theoretically that depending on its oxidation state, PANI exhibits two spectral absorption regions . The first one in the UV region and refers to the leucomeraldine form.…”
Section: Resultsmentioning
confidence: 80%
“…. As largely reported in the literature, either experimentally or theoretically that depending on its oxidation state, PANI exhibits two spectral absorption regions . The first one in the UV region and refers to the leucomeraldine form.…”
Section: Resultsmentioning
confidence: 80%
“…Figure depicts the FTIR spectra of the polyaniline before and after doping with ZnSe nanoparticles. The FTIR spectra of the undoped polyaniline showed absorption bands at 3248, 2993, 1562, 1458, 1288 – , and 1127 cm −1 corresponding to NH stretching vibrations, The aromatic CH stretching, CN stretching of quinoid rings, CN stretching of benzoid rings, aromatic CN stretching and CH in plane bending vibration, respectively . The FTIR spectra of the polyaniline doped ZnSe nanoparticles showed that the intensity of the undoped polyaniline peaks is decreased and the NH stretching peak is shifted by 16 to 3264 cm −1 , implying the interaction between ZnSe and polyaniline molecules.…”
Section: Resultsmentioning
confidence: 99%
“…It was proved that the addition of small amounts of inorganic nanoparticles into the polymer matrix can improve the optical, mechanical, and electrical properties . Among all tested polymers, polyaniline is the most premeditated polymer for its facile synthesis, high stability and high conductivity . Moreover, Zinc selenide (ZnSe) is II–VI semiconducting materials, which has optical band gap of 2.7 eV enables it to be used in diverse applications such as photovoltaic solar cells and blue diode lasers .…”
Section: Introductionmentioning
confidence: 99%
“…Conducting polymers such as polyaniline (PAn), polypyrrole (PPy), poly( N ‐methylpyrrole) (PNMPy), polythiophene (PTh), and their derivatives with different electrical or electrochemical properties have been studied extensively because of their many potential applications . The electrochemical stability of poly‐ N ‐substituted pyrrole is better than that of the PPy .…”
Section: Introductionmentioning
confidence: 99%